2012
DOI: 10.1111/j.1601-183x.2012.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in DNMT3B and increased global DNA methylation is associated with suicide attempts in psychiatric patients

Abstract: Recently, a significant epigenetic component in the pathology of suicide has been realized. Here we investigate candidate functional SNPs in epigenetic-regulatory genes, DNMT1 and DNMT3B, for association with suicide attempt (SA) among patients with co-existing psychiatric illness. In addition, global DNA methylation levels [5-methyl cytosine (5-mC%)] between SA and psychiatric controls were quantified using the Methylflash Methylated DNA Quantification Kit. DNA was obtained from blood of 79 suicide attempters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 32 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…Rs2424932 is present in the 3′-UTR of the DNMT3B gene. In addition, the A/G polymorphism at this locus can create alternative transcription factors binding site (TFBSs), hence it is plausible to suggest that this SNP could potentially alter DNMT3B gene regulation [23]. Rs2424913 is one polymorphism in promoter region of DNMT3B.…”
Section: Discussionmentioning
confidence: 99%
“…Rs2424932 is present in the 3′-UTR of the DNMT3B gene. In addition, the A/G polymorphism at this locus can create alternative transcription factors binding site (TFBSs), hence it is plausible to suggest that this SNP could potentially alter DNMT3B gene regulation [23]. Rs2424913 is one polymorphism in promoter region of DNMT3B.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, using different behavioral and electrophysiological protocols, our laboratory recently reported that forebrain-specific knockout of DNMT3a led to learning and memory deficits and impairments in synaptic plasticity, however DNMT1 KO mice were indistinguishable from control mice (Morris et al , 2014). Recent work in humans and in animal models suggests that aberrant DNA methylation and expression of DNMTs may be causal or contributing factors in a variety of psychiatric disorders including major depressive disorder, anxiety disorders, and schizophrenia (Grayson et al , 2005; Murgatroyd & Spengler, 2012; Chouliaras et al , 2013; Murphy et al , 2013; Hing et al , 2014; Murphy et al , 2015). Indeed, data in humans implicate different DNMT isoforms in the etiology of distinct neuropsychiatric syndromes including suicide (DNMT3b) and schizophrenia (DNMT1) (Grayson et al , 2005; Murphy et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in humans and in animal models suggests that aberrant DNA methylation and expression of DNMTs may be causal or contributing factors in a variety of psychiatric disorders including major depressive disorder, anxiety disorders, and schizophrenia (Grayson et al , 2005; Murgatroyd & Spengler, 2012; Chouliaras et al , 2013; Murphy et al , 2013; Hing et al , 2014; Murphy et al , 2015). Indeed, data in humans implicate different DNMT isoforms in the etiology of distinct neuropsychiatric syndromes including suicide (DNMT3b) and schizophrenia (DNMT1) (Grayson et al , 2005; Murphy et al , 2013). Furthermore, a recent study reported that antidepressant medications specifically inhibit the activity of DNMT1 via inhibition of the histone methyltransferase G9a (Zimmermann et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms located in introns may affect gene expression by altering mRNA splicing (Moyer et al, 2011), and this could affect cancer susceptibility (Malkinson and You, 1994). A case-control study in a Polish population reported that DNMT1 rs8101626 A N G polymorphism was not associated with ovarian cancer (Mostowska et al, 2013), and Murphy et al did not observe an association between the DNMT1 rs8101626 A N G polymorphism and suicide attempts in psychiatric patients (Murphy et al, 2013). An investigation of the DNMT3A rs34048824 polymorphism found that it did not affect methylation of long interspersed nucleotide elements (LINE-1) in healthy adults in Singapore (Inoue-Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 96%